Mitochondrial transcription factor A (TFAM) rs1937 and AP endonuclease 1 (APE1) rs1130409 alleles are associated with reduced cognitive performance. (3rd April 2017) - Lillenes, Meryl S.; Støen, Mari; Günther, Clara-Cecilie; Selnes, Per; Stenset, Vidar T.V.; Espeseth, Thomas; Reinvang, Ivar; Fladby, Tormod; Tønjum, Tone
Highlights: Mitochondrial dysfunction and DNA damage is connected to ageing and neurodegeneration. Base excision repair (BER) is the major pathway for repairing oxidative damage events in chromosomal and mitochondrial DNA. Deficient BER activity has been detected in brain ageing and neurodegeneration. Alleles in mitochondrial transcription factor A (TFAM) and AP endonuclease 1 (APE1) are associated with reduced cognitive performance. Single nucleotide polymorphisms (SNPs) in BER and TFAM genes are potential diagnostic biomarkers for cognitive function. Abstract: Mitochondrial dysfunction and DNA damage is intimately connected to ageing and neurodegeneration, including Alzheimer's disease (AD). A particular culprit in this context is oxidative stress, which is a result of increased reactive oxygen species (ROS) due to hyperactive or dysfunctional mitochondria and/or reduced DNA repair capacity. Base excision repair (BER) is the major pathway for repairing oxidative damage events in chromosomal and mitochondrial DNA. Defects in BER have been detected in ageing and neurodegeneration. Mitochondrial transcription factor A (TFAM) plays an important role in the maintenance of mitochondrial DNA integrity. The present study investigated single nucleotide polymorphisms (SNPs) in the genes encoding the BER components MutYH, OGG1, APE1, PolB and PolG and the gene encoding mitochondrial TFAM in a cohort of 161 AD patients, 96 non-AD patient controls (PC) and 192 healthy controls (HC). Notably, the minor allele carriers of APE1 rs1130409 and the common allele carriers of TFAM rs1937 were associated with reduced mini-mental state examination score in AD patients, PC and HC, with no distinction of SNP frequencies in either of these sub-groups. Collectively, the results suggest an association between DNA maintenance and decline in cognitive function. These studies enlighten the normal brain aging process and point to potential new biomarkers for cognitive function and impairment.